Gastric perforation due to a muscular wall defect in a 5-month-old boy:a case report and literature review - J.F. Bao; W. Dong; Y. Mei; W.J. Zhuang (Elsevier, 2019)
Background: Spontaneous gastric rupture due to the muscular wall defect usually occurs on the premature neonate while rarely occurs on the infant. Case summary: We are now describing a case of a 5-month-old boy presenting sudden onset of extensive abdominal distension. Emergency abdominal CT showed pneumoperitoneum. Laparotomy showed a perforation at the level of the small gastric curvature, measuring 7*5 cm in diameter. The gastric perforation was repaired by simple suture. The patient recovered uneventfully. Conclusion: Spontaneous gastric rupture due to the muscular wall defect could occurs on the infant. Keywords: Gastric muscular wall defect, Gastric rupture, Infant